2013
DOI: 10.1186/1472-6882-13-42
|View full text |Cite
|
Sign up to set email alerts
|

Citrus aurantium L. essential oil exhibits anxiolytic-like activity mediated by 5-HT1A-receptors and reduces cholesterol after repeated oral treatment

Abstract: BackgroundThe current treatments for anxiety disorders and depression have multiple adverse effects in addition to a delayed onset of action, which has prompted efforts to find new substances with potential activity in these disorders. Citrus aurantium was chosen based on ethnopharmacological data because traditional medicine refers to the Citrus genus as useful in diminishing the symptoms of anxiety or insomnia, and C. aurantium has more recently been proposed as an adjuvant for antidepressants. In the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
69
1
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(87 citation statements)
references
References 44 publications
(57 reference statements)
6
69
1
6
Order By: Relevance
“…The most noteworthy among these are C. x sinensis (Faturi et al, 2010) and C. x limon (Ceccarelli et al, 2004) in rats, and C. x latifolia (Gargano et al, 2008) and C. x aurantium (Carvalho-Freitas, Costa, 2002;Pultrini et al, 2006) in mice. Sedative and anxiolytic-like effects have been described for the EO obtained from the peel of Citrus x aurantium in rats and mice (Leite et al, 2008;Costa et al, 2013). However, the literature does not present reports of their anesthetic effects on fish.…”
Section: Introductionmentioning
confidence: 99%
“…The most noteworthy among these are C. x sinensis (Faturi et al, 2010) and C. x limon (Ceccarelli et al, 2004) in rats, and C. x latifolia (Gargano et al, 2008) and C. x aurantium (Carvalho-Freitas, Costa, 2002;Pultrini et al, 2006) in mice. Sedative and anxiolytic-like effects have been described for the EO obtained from the peel of Citrus x aurantium in rats and mice (Leite et al, 2008;Costa et al, 2013). However, the literature does not present reports of their anesthetic effects on fish.…”
Section: Introductionmentioning
confidence: 99%
“…Aromatherapy the alternative medicinal system describes the healing effect by essential oils from plant origin. The volatile oil from citrus fruit has already been reported by several researchers by hydrodistillation (Vashist and Sharma, 2013;Vashist et al, 2014;Costa et al, 2013;Hamdan et al, 2013) and using supercritical carbon dioxide (Atti-Santos et al, 2005). The volatile oil fraction in citrus peels present in the oil duct, oil gland or oil cells beneath the layer of epithelial cells (Fig.…”
Section: Introductionmentioning
confidence: 71%
“…The oil cells when get ruptured the oil starts to ooze out of the cell through the duct, which get formed during rupturing of surrounding cell layers. It has been reported that populations in several countries opt to the preparations obtained from Citrus species to treat problems related to the nervous system, especially symptoms of anxiety or insomnia (Costa et al, 2013). This may be because of the less side effects from such preparations, which again underlines the importance of citrus extracts in alternative medicinal system.…”
Section: Introductionmentioning
confidence: 99%
“…It was also shown that this EO has an effect similar to diazepam when intraperitoneally administered in mice (Lima et al, 2013). This monoterpene is present at high percentages in Citrus aurantium EO (97.83%) having anxiolytic activity (Pultrini et al, 2006;Costa et al, 2013.). Furthermore, a product from limonene oxidation, limonene epoxide, also showed anxiolytic characteristics (De Almeida et al, 2012).…”
Section: Discussionmentioning
confidence: 99%